Synergistic Antitumour Properties of viscumTT in Alveolar Rhabdomyosarcoma - Rahel Mascha Stammer; Susann Kleinsimon; Jana Rolff; Sebastian Jäger; Angelika Eggert; Georg Seifert; Catharina I. Delebinski (Journal of Immunology Research)
Aqueous mistletoe extracts from the European mistletoe (Viscum album) contain mainly mistletoe lectins and viscotoxins as cytotoxic compounds. Lipophilic triterpene acids, which do not occur in conventional mistletoe preparations, were solubilised with β-cyclodextrins. The combination of an aqueous extract (viscum) and a triterpene-containing extract (TT) recreated a whole mistletoe extract (viscumTT). These extracts were tested on rhabdomyosarcoma in vitro, ex vivo, and in vivo with regard to anticancer effects. Viscum and viscumTT inhibited cell proliferation and induced apoptosis effectively in a dose-dependent manner in vitro and ex vivo, whereas TT showed only moderate inhibitory effects. viscumTT proved to be more effective than the single extracts and displayed a synergistic effect in vitro and a stronger effect in vivo. viscumTT induced apoptosis via the extrinsic and intrinsic pathways, evidenced by the loss of mitochondrial membrane potential and activation of CASP8 and CASP9. CASP10 inhibitor inhibited apoptosis effectively, emphasising the importance of CASP10 in viscumTT-induced apoptosis. Additionally, viscumTT changed the ratio of apoptosis-associated proteins by downregulation of antiapoptotic proteins such as XIAP and BIRC5, thus shifting the balance towards apoptosis. viscumTT effectively reduced tumour volume in patient-derived xenografts in vivo and may be considered a promising substance for rhabdomyosarcoma therapy.